VIRTU: Student Behavior Reporting App - BINTI MAIJAL, AMYZA APIVA; MAT REJAB, MAZIDAH (Applied Information Technology And Computer Science, 2026)
Student behavior management in Malaysian secondary schools currently relies on SSDM (Sistem Sahsiah Diri Murid), which requires teachers to manually login through school accounts, type student names and IC numbers for identification, leading to time-consuming processes and data entry errors. This study develops VIRTU, an enhanced digital student behavior reporting system that utilizes QR code technology to streamline the existing SSDM workflow for SMK Bangsar. The system was developed using Waterfall methodology, implemented with Flutter mobile applications, Firebase backend, and web-based administrative dashboard to replace manual student identification with automated QR code scanning. The system features role-based access control, real-time notifications, and comprehensive reporting capabilities. Expected outcomes include reduced manual workload, improved tracking accuracy, and enhanced stakeholder communication, demonstrating strong potential for upgrading existing SSDM implementations across Malaysian secondary schools